Virtual Synthetic Aperture Radar Target Based on a Miniaturized Monostatic Digital Delay Transponder - Stelzig, Michael; Benedikter, Andreas; Horn, Ralf; Jaeger, Marc; Keller, Martin; Scheiber, Rolf; Krieger, Gerhard; Vossiek, Martin (IEEE Microwave and Wireless Components Letters, 2021)
The ice penetrating capability of low-frequency radar systems may offer a unique potential for the detection, localization, and guidance of exploratory ice-penetrating probes for cryospheric applications. As these probes exhibit a comparably small radar cross section (RCS), reliable detection, especially in high clutter surroundings, such as ice sheets, is prevented. As a solution, a miniaturized monostatic digital delay transponder is developed and tested regarding its functionality with an airborne synthetic aperture radar (SAR) sensor.
Keywords: Transponders; Radar; Syntethic aperture radar (SAR); Radar cross-sections (RCS); Delays; Probes; Ice; Pulse compression